Transcranial Direct Current Stimulation: Considerations for Research in Adolescent Depression - Lee, Jonathan C.; Lewis, Charles P.; Daskalakis, Zafiris J.; Croarkin, Paul E. (Frontiers in Psychiatry, 2017)
Adolescent depression is a prevalent disorder with substantial morbidity and mortality. Current treatment interventions do not target relevant pathophysiology and are frequently ineffective, thereby leading to a substantial burden for individuals, families, and society. During adolescence the prefrontal cortex undergoes extensive structural and functional changes. Recent work suggests that frontolimbic development in depressed adolescents is delayed or aberrant. The judicious application of noninvasive brain stimulation techniques to the prefrontal cortex may present a promising opportunity for durable interventions in adolescent depression. Transcranial direct current stimulation (tDCS) applies a low-intensity, continuous current that alters cortical excitability. While this modality does not elicit action potentials, it is thought to manipulate neuronal activity and neuroplasticity. Specifically, tDCS may modulate N-methyl-D-aspartate receptors and L-type voltage-gated calcium channels and effect changes through long-term potentiation or long-term depression-like mechanisms. This mini-review will consider the neurobiological rationale for developing tDCS protocols in adolescent depression, review existing work in adult mood disorders, survey existing the tDCS literature in adolescent populations, review safety studies, and discuss distinctive ethical considerations in work with adolescents.